Cartografia da publi-cidade: uma narrativa rizomática da cidade como mídia - Fernandes, Arion (2019)
This dissertation starts from the question of how the territorializations and reterritorializations of the advertising from the actions observed in the public space, aiming to analyze the formal advertising deterritorializations from the tactical actions that occur in the public space. For this, it starts from the discussion of the theoretical axes and its intersection: the daily, the city and the advertising. The daily is understood from the crowd productive action, aligning the concepts of Michel de Certeau (1994) and Hardt & Negri (2014). The city is proposed as a media, elaborated based on the possibilites of interaction and plural access, supported by Eliséo Verón (1997), and from the vision of the city as communicational flows of Massimo Di Felice (2009). In the third theoretical element, the advertising is discussed based on the concepts of extramedia of Dominique Quessada (2003) and publicization of Vander Casaqui (2011), dealing with the transformation movements and new practices on the advertising field. The study has the cartography as a methodological course, being developed from the rhizomatic perspective and the procedures applied according to the varieties of cartographic attention of Virgínia Kastrup (2007). Based on the collected data, the rhizome of advertising overflows is designed. Starting from this stratified map, the study has as result the rhizome of the reterritorialities of advertising, built from four plateaus: the city as a brand performance space; the daily as an environment of references and causes for the advertising; the advertising with the new kinds of delivery, non-defined shapes and socially responsible actions; and new practices characterized by opened creation, multidisciplinarity and jobs for projects. The perspective of these four plateaus gives origin to the publi-city concept: actuation proposal more responsible and engaged to the urban environment and to the society.